Diversifikasi Olahan Nira Tebu Melalui Diseminasi Teknologi Mesin Pemeras Tebu di Desa Karangbener Kecamatan Bae Kabupaten Kudus - Sumarno Sumarno; Achmad Buchori; Carsoni Carsoni (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Dissemination of technology products to the community aims to improve the welfare of sugar cane farmers in Karangbener Village, Bae District, Kudus Regency. The problem faced by farmers is the low price of sugar cane due to nonstandard yields and the low capacity of the sugar factory to receive sugar cane farmers in the harvest season. The strategy used is processing sugar cane by diversifying the processing of sugar cane through the dissemination of sugar cane presses. The strategy includes sugarcane cultivation socialization activities, diversification of sugar cane processing, training on the use of sugar cane presses, financial management training and training in selling and marketing sugarcane juice products to Sari Rejo and Bangun Harjo farmer groups with a total of 31 members. The results of the activity of making 3 units of sugarcane squeezer machines which have been handed over to farmer groups, the ability of farmer group members to diversify sugarcane juice preparations, the ability to operate and maintain sugarcane squeezer machines, and have an understanding of management and marketing of sugarcane processed diversified products